Calibrated ages of Haukkasuo HAU (HAK (A800+200)) peat core from Finland - Mäkilä, Markku (PANGAEA, 2021)
Calibrated ages of a high-resolution peat core from the Past Global Changes - Carbon in Peat on EArth through Time (PAGES_C-PEAT) Project.
Keywords: C-PEAT; Peatland